Targeted inhibition of Janus kinases abates interfon gamma-induced invasive behaviour of fibroblast-like synoviocytes. (7th December 2017) - Karonitsch, Thomas; Beckmann, Denise; Dalwigk, Karolina; Niederreiter, Birgit; Studenic, Paul; Byrne, Ruth A; Holinka, Johannes; Sevelda, Florian; Korb-Pap, Adelheid; Steiner, Günter; Smolen, Josef S; Pap, Thomas; et al.
Abstract: Objectives: The aim was to explore the function of the T-cell cytokine IFNγ for mesenchymal tissue remodelling in RA and to determine whether IFNγ signalling controls the invasive potential of fibroblast-like synoviocytes (FLS). Methods: To assess architectural responses, FLS were cultured in three-dimensional micromasses. FLS motility was analysed in migration and invasion assays. Signalling events relevant to cellular motility were defined by western blots. Baricitinib and small interfering RNA pools were used to suppress Janus kinase (JAK) functions. Results: Histological analyses of micromasses revealed unique effects of IFNγ on FLS shape and tissue organization. This was consistent with accelerated migration upon IFNγ stimulation. Given that cell shape and cell motility are under the control of the focal adhesion kinase (FAK), we next analysed its activity. Indeed, IFNγ stimulation induced the phosphorylation of FAK-Y925, a phosphosite implicated in FAK-mediated cell migration. Small interfering RNA knockdown of JAK2, but not JAK1, substantially abrogated FAK activation by IFNγ. Correspondingly, IFNγ-induced FAK activation and invasion of FLS was abrogated by the JAK inhibitor, baricitinib. Conclusion: Our study contributes insight into the synovial response to IFNγ and reveals JAK2 as a potential therapeutic target for FLS-mediated joint destruction in arthritis, especially in RA.